Comparative Effect Analysis of Commercial Profit and Fiscal Profit at PT. X in Surabaya - Arita Ratnasari; Tjandra Wasesa; Diana Zuhro; Heri Toni Hendro; Sutini Sutini; Wiratna Wiratna; Achmad Daengs GS (Jurnal Multidisiplin Sahombu, 2026)
Financial statements provide a final picture of a company’s financial condition and performance and are used as a basis for managerial, investment, and taxation decisions. In Indonesia, commercial financial statements are prepared under Financial Accounting Standards, whereas fiscal financial statements follow tax regulations. This study compares commercial profit and fiscal profit at PT. X in Surabaya and identifies the fiscal corrections required to reconcile the two measures. The research uses a descriptive-comparative approach based on PT. X’s 2016 financial statements, with analysis focused on permanent and temporary differences in deductible costs and depreciation. The results show positive fiscal corrections of Rp 93,498,981, consisting of Rp 42,225,000 in permanent differences and Rp 51,273,981 in temporary differences. These corrections increase taxable profit from commercial profit before tax of Rp 704,999,954.82 to Rp 798,498,935.82 and raise income tax payable to Rp 175,692,491.82, or Rp 20,572,436.88 above the amount before correction. The findings confirm that consistent fiscal reconciliation is necessary to prevent misstatement of taxable income and to align corporate bookkeeping with applicable tax provisions.